THE SIGNIFICANCE OF AUTUMNAL SEA ICE BIOTA IN THE ECOSYSTEM OF ICE-COVERED POLAR SEAS (17th Symposium on Polar Biology) - ホシアイ, タカオ; タニムラ, アツシ; クドウ, サカエ; HOSHIAI, Takao; TANIMURA, Atsushi; KUDOH, Sakae (National Institute of Polar Research, 1996)
P(論文) The autumnal sea ice proliferation occurs at Syowa Station. The algal cells produced support the ice meiofauna and possibly planktonic and benthic consumers. However, the autumnal bloom of ice algae has received little attention from polar biologists during long-term history of sea ice biota research. The geographical distribution, and ecological importance and function of the autumnal ice algal community is reviewed and compared with the spring ice community. departmental bulletin paper